2022
DOI: 10.1186/s13018-022-03376-y
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport after conservative versus surgical treatment for pubalgia in athletes: a systematic review

Abstract: Background To assess the time required to return to sport (RTS) after conservative versus surgical treatment in athletes for pubalgia. Methods The PRISMA guidelines were followed. Pubmed, SportDiscus and Web of Science were last accessed on September 2022. All the studies investigating the time to RTS after conservative versus surgical treatment in athletes for pubalgia. Results In total, 33 studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For these reasons, we recommend that future research explores the impact of the execution speed of shoulder exercises on scapular neuromuscular control. In addition, it would be valuable to investigate the potential effects of resistance exercises in preventing fatigue and reducing the risk of injury 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, we recommend that future research explores the impact of the execution speed of shoulder exercises on scapular neuromuscular control. In addition, it would be valuable to investigate the potential effects of resistance exercises in preventing fatigue and reducing the risk of injury 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it would be valuable to investigate the potential effects of resistance exercises in preventing fatigue and reducing the risk of injury. 33…”
Section: Limitationsmentioning
confidence: 99%
“…Expanding the scope, Serafim et al, through a comprehensive review, inferred that athletes opting for surgery often rejoin their sport sooner than those adopting conservative treatments. Yet, they underscore the primacy of weighing conservative strategies before leaping to surgical decisions [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…A previous systematic review done by Serafim et al found that athletes who underwent surgery for AP returned to sport earlier than those receiving conservative treatment alone [ 10 ]. This may explain why elite-level athletes, in comparison with their recreational counterparts, may opt for earlier surgical fixation following a diagnosis of AP.…”
Section: Introductionmentioning
confidence: 99%